Estimation of Global Solar Radiation using Angstrom and Gopinathan Model on Sunshine Hour and Temperature in Highland, Nepal - Saud, Jay S.; Shrestha, Prakash M.; Joshi, Usha; Tiwari, Babu R.; Karki, Indra B.; Poudyal, Khem N. (Molung Educational Frontier, 2023)
In developing countries like Nepal, the direct measurement of global solar radiation (GSR) is difficult. So, the estimation of GSR is carried out at Jumla (29°16′ N, 82° 11′ E and about 2347 m altitude) for the year 2015 and 2017 using regression technique to the meteorological parameters on Angstrom model, Gopinathan and Olomiyesan- Oyedum models. Among three models, Olomiyesan and Oyedum model is better than other models. Its empirical constants a=0.38, b=0.10 and c=0.09 are found. The values of statistical errors MBE, MPE and RMSE are smaller than other models. Similarly, the coefficient of determination (R2=0.89) is greater than other models. Finally, the finding empirical constants and meteorological parameters sunshine hour, and temperature are used to estimate the GSR for the year 2017. In addition to this, the annual average GSR for the year 2015 and 2017 are found to be 18.86 MJ/m2/day and 17.50 MJ/m2/day respectively. It is concluded that the finding empirical constants are used to estimate the GSR and solar energy at similar geographical location of Nepal.